2020
DOI: 10.5114/aoms.2019.85244
|View full text |Cite
|
Sign up to set email alerts
|

MiR-376c-3p targets heparin-binding EGF-like growth factor (HBEGF) to inhibit proliferation and invasion in medullary thyroid carcinoma cells

Abstract: Introduction: Aggressive medullary thyroid carcinomas (MTC) have a high mortality rate and the treatment for patients diagnosed with advanced MTC is comparatively ineffective. We hence aimed to test the effects of miR-376c-3p on MTC and to explore the relevant mechanism. Material and methods: Cell Counting Kit-8 (CCK-8) and soft agar colony formation assay were applied to evaluate the proliferation of transfected MZ-CRC-1 cells. Wound healing and transwell assay were employed to evaluate MTC cell migration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…3 ). HB-EGF stands out from all other potential target genes given its involvement in many other cancers, such as gliomagenesis [ 46 ], breast cancer [ 47 ], and medullary thyroid carcinoma [ 48 ]. In addition, previous studies also showed that HB-EGF mediates proliferation and apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ). HB-EGF stands out from all other potential target genes given its involvement in many other cancers, such as gliomagenesis [ 46 ], breast cancer [ 47 ], and medullary thyroid carcinoma [ 48 ]. In addition, previous studies also showed that HB-EGF mediates proliferation and apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports utilized CCK-8 cell viability assays to assess the safety of the three at the cellular level. 39 We utilized ARPE-19 cells and HUVECs, commonly encountered at CNV lesion sites, to observe the cytotoxicity of 5-FITC-CPP, 5-FCR, and 5-FCC. Post-intervention, there were no significant changes in cell morphology or activity compared to the control group, displaying results similar to those in Vives et al’s study.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al [24] reported a decrease in the expression of N-cadherin and Vimentin, and an increase in the expression of E-cadherin and ZO-1 with miR-376c-3p transfer, which reduces tumour aggressiveness and invasiveness in MTC cell lines. Thus, they demonstrated the protective effect of ZO-1 against tumour invasiveness.…”
Section: Discussionmentioning
confidence: 99%